Comprehensive Assessment of Implementation Factors Related to Worksite Exercise in Firefighters. Issue 1 (20th October 2021) - Lane, Charity L.; Brady, O'Dane; Mayer, John M.
Abstract : Objective: This study sought to identify key implementation factors to a 12-month worksite exercise intervention in career firefighters. Methods: Implementation factors related to the hybrid type 1 effectiveness-implementation trial were assessed by exercise adherence, implementation questionnaires, focus groups, and observations from stakeholders. Results: The primary identified implementation themes spanned intrapersonal, interpersonal, and institutional factors including: 1. Time and desire to exercise on shift; 2. Financial incentives to exercise; 3. Structured fitness programs; 4. Group competition, cohesion, and camaraderie; 5. Leadership engagement and support; and 6. Health, fitness, and occupational preparedness benefits. Conclusions: Future worksite exercise programs should address the barriers and facilitators identified herein and consider utilizing a hybrid delivery approach combining supervised and telehealth exercise interventions to optimize enthusiasm, adherence and improve safety and health.